Case study : financial statement analysis of petrovietnam southern gas joint stock company = Phân tích báo cáo tài chính công ty cổ phần kinh doanh khí hóa lỏng Miền Nam - Bùi, Thanh Tùng (2021)
Financial analysis, for a long time, has been among the most important procedures for any professional participant in the financial market. However, financial analysis and its application only receive minor interest in undergraduate program for students in University of Languages and International Studies. The goal of the case study is to help create a sufficient analysis system practically applicable for the real-time analysis, and yet available and suitable for the usage of undergraduate student. During the research, the researcher has demonstrated the application in the specific case of Petrovietnam Southern Gas Joint Stock Company, a developing company listed in HNX Exchange Market. The research has assessed the company’s current financial situation for the last 5 year in order to come to some conclusions relating to the company financial conditions, operating performance and cash flow. Although the research is far from perfection, the researcher hopes that it will provide the readers with an adequate system for financial analysis, and would attract more attention to the related study in the near future.